Conceptual Framework of Inquiry-Creative-Process Learning Model to Promote Critical Thinking Skills of Physics Prospective Teachers (Jurnal Pendidikan Fisika Indonesia, 2019)
Critical thinking has become a major competency of higher education learning in Indonesia; therefore, a specific learning model that is oriented towards improving students' critical thinking skills is important to be developed. This study aims to develop an Inquiry Creative Process (ICP) learning model to promote critical thinking skills of physics prospective teachers. This research is the first step of development research which produce learning model with valid criteria on content validity and construct validity aspects. The validation of ICP learning model has been done through focus group discussion (FGD) mechanism involving 5 experts as validator. The data of the validation results of the model were analyzed descriptively by averaging the validation score. Validation results show that the validity level (Va) of 4.12. The conceptual framework and validation results of the ICP learning model are described in this article.Berpikir kritis telah menjadi kompetensi utama pembelajaran tingkat pendidikan tinggi di Indonesia, sehingga model pembelajaran yang spesifik berorientasi ke arah peningkatan keterampilan berpikir kritis mahasiswa menjadi penting untuk dikembangkan. Penelitian ini bertujuan mengembangkan model pembelajaran Inquiry Creative Process (ICP) untuk melatih keterampilan berpikir kritis mahasiswa calon guru fisika. Penelitian ini merupakan langkah awal penelitian pengembangan yang menghasilkan produk model pembelajaran dengan kriteria valid pada aspek-aspek validitas isi (content validity) dan validitas konstruk (construct validity). Validasi model pembelajaran ICP dilakukan melalui mekanisme focus group discussion (FGD) dengan melibatkan 5 orang pakar selaku validator. Data hasil validasi model dianalisis secara deskriptif dengan merata-rata skor hasil validasi. Hasil validasi menunjukkan tingkat kevalidan (Va) model pembelajaran ICP sebesar 4,12 berada pada kategori valid. Kerangka konseptual dan hasil validasi model pembelajaran ICP dijabarkan dalam artikel ini.Â